2012
DOI: 10.4161/rna.9.1.18008
|View full text |Cite
|
Sign up to set email alerts
|

Small RNAs of theBradyrhizobium/Rhodopseudomonaslineage and their analysis

Abstract: Evguenieva-Hackenberg (2012) Small RNAs (sRNAs) play a pivotal role in bacterial gene regulation. However, the sRNAs of the vast majority of bacteria with sequenced genomes still remain unknown since sRNA genes are usually difficult to recognize and thus not annotated. Here, expression of seven sRNAs (BjrC2a, BjrC2b, BjrC2c, BjrC68, BjrC80, BjrC174 and BjrC1505) predicted by genome comparison of Bradyrhizobium and Rhodopseudomonas members, was verified by RNA gel blot hybridization, microarray and deep sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
39
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 60 publications
1
39
0
2
Order By: Relevance
“…Recent high-throughput analyses revealed that these α-proteobacterial species harbor hundreds of RNAs with regulatory potential. [5][6][7][8][9][10][11][12] It is the challenge now to understand their physiological roles and the underlying molecular mechanisms. A systematic comparison of the sRNA repertoires of selected model organisms may help to understand the commonalities and differences between these phylogenetically and ecologically related bacteria.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent high-throughput analyses revealed that these α-proteobacterial species harbor hundreds of RNAs with regulatory potential. [5][6][7][8][9][10][11][12] It is the challenge now to understand their physiological roles and the underlying molecular mechanisms. A systematic comparison of the sRNA repertoires of selected model organisms may help to understand the commonalities and differences between these phylogenetically and ecologically related bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…This view is supported by the large amount of cis-and trans-encoded sRNAs detected by genome-wide analyses in these plant-associated bacteria. [5][6][7][8][9][10][11][12] Since conservation of sRNAs is mostly limited to closely related bacteria, the phylogenetic relationships between α-rhizobia and Agrobacterium species allow the functional comparison of sRNAs with different degrees of conservation in function and regulation. Here, we summarize the current knowledge on the non-coding RNome as inferred from genome-wide surveys and discuss the incipient insights into biological functions and mechanisms of riboregulation in these organisms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In many bacteria, including cyanobacteria, small regulatory RNAs (sRNAs) have been reported as important regulators of gene expression (25)(26)(27)(28)(29). By base pairing with their target mRNA(s), small RNAs can interfere with the ribosome binding site or other sequence stretches and, consequently, alter mRNA translation and stability.…”
mentioning
confidence: 99%